Intense Beauty Requires Intense Pleasure - Brielmann, Aenne A.; Pelli, Denis G. (Frontiers in Psychology, 2019)
At the beginning of psychology, Fechner (1876) claimed that beauty is immediate pleasure, and that an object’s pleasure determines its value. In our earlier work, we found that intense pleasure always results in intense beauty. Here, we focus on the complementary question: Is intense pleasure necessary for intense beauty? If so, the inability to experience pleasure (anhedonia) should prevent the experience of intense beauty. We asked 757 participants to rate how intensely they felt beauty from each image. We used 900 OASIS images along with their available valence (pleasure vs. displeasure) and arousal ratings. We then obtained self-reports of anhedonia (TEPS), mood, and depression (PHQ-9). Across images, beauty ratings were closely related to pleasure ratings (r = 0.75), yet unrelated to arousal ratings. Only images with an average pleasure rating above 4 (of a possible 7) often achieved (> 10%) beauty averages exceeding the overall median beauty. For normally beautiful images (average rating > 4.5), the beauty ratings were correlated with anhedonia (r ~ -0.3) and mood (r ~ 0.3), yet unrelated to depression. Comparing each participant’s average beauty rating to the overall median, none of the most anhedonic participants exceeded the median, whereas 50% of the remaining participants did. Thus, both general and anhedonic results support the claim that intense beauty requires intense pleasure. In addition, follow-up repeated measures showed that shared taste contributed 19% to beauty-rating variance, only one third as much as personal taste (58%). Addressing age-old questions, these results indicate that beauty is a kind of pleasure, and that beauty is more personal than universal, i.e., 1.7 times more correlated with individual than with shared taste.